2011
DOI: 10.1038/nature10536
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing in plants is mediated by an N-end rule pathway for protein destabilization

Abstract: The majority of eukaryotic organisms rely on molecular oxygen for respiratory energy production. When the supply of oxygen is compromised, a variety of acclimation responses are activated to reduce the detrimental effects of energy depletion. Various oxygen-sensing mechanisms have been described that are thought to trigger these responses, but they each seem to be kingdom specific and no sensing mechanism has been identified in plants until now. Here we show that one branch of the ubiquitin-dependent N-end rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

24
1,008
5
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 682 publications
(1,041 citation statements)
references
References 36 publications
24
1,008
5
4
Order By: Relevance
“…It is important to note that the expression of these genes under aerobic condition was as high as that in wild type under anaerobic condition (Gibbs et al 2011). In Arabidopsis seedlings, overexpressing RAP2.2 (Hinz et al 2010) or its closest homolog RAP2.12 (Licausi et al 2011) anaerobic carbon metabolism genes were strongly induced during low oxygen stress; changes in gene expression were accompanied by improved survival of the seedlings to flooding-induced low oxygen stress. Microarray analysis followed by quantitative RT-PCR for the comparison of genes induction by hypoxia treatment in wild type and Arabidopsis silenced in both RAP2.2 and RAP2.12 showed a reduced induction of anaerobic carbon metabolism genes in miRNA lines and confirmed that these transcription factors are required for the regulation of hypoxia-induced genes (Licausi et al 2011;Hinz et al 2010).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that the expression of these genes under aerobic condition was as high as that in wild type under anaerobic condition (Gibbs et al 2011). In Arabidopsis seedlings, overexpressing RAP2.2 (Hinz et al 2010) or its closest homolog RAP2.12 (Licausi et al 2011) anaerobic carbon metabolism genes were strongly induced during low oxygen stress; changes in gene expression were accompanied by improved survival of the seedlings to flooding-induced low oxygen stress. Microarray analysis followed by quantitative RT-PCR for the comparison of genes induction by hypoxia treatment in wild type and Arabidopsis silenced in both RAP2.2 and RAP2.12 showed a reduced induction of anaerobic carbon metabolism genes in miRNA lines and confirmed that these transcription factors are required for the regulation of hypoxia-induced genes (Licausi et al 2011;Hinz et al 2010).…”
mentioning
confidence: 99%
“…Instead it is thought that oxygen availability in plants is sensed via changes in redox status (NADH/NAD ratio), reactive oxygen species (ROS), NO, and energy status of the cell (ATP content). It is only recently that the N-end rule pathway (NERP) for protein destabilization described first in animals (Hu et al 2005) was proposed as an indirect mechanism for oxygen sensing in plants (Gibbs et al 2011;Licausi et al 2011). Transcription factors RAP2.2, RAP2.12, HRE1 and HRE2 of the group-VII Ethylene Response Factors (ERF) revealed as key players in the regulation of low oxygen stress-responsive genes by experiments aiming at comprehensive insight into Arabidopsis transcriptome/translatome responses to hypoxia and anoxia proved to be subjected to oxygen-dependent posttranslational modification through the NERP for protein degradation (Licausi et al , 2011Gibbs et al 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations